2020
DOI: 10.1038/s41598-020-72583-6
|View full text |Cite
|
Sign up to set email alerts
|

Batch and continuous fixed bed adsorption of heavy metals removal using activated charcoal from neem (Azadirachta indica) leaf powder

Abstract: The present investigate was intended for adsorption of heavy metals i.e. Pb, Cu, Cr, Zn, Ni and Cd onto activated charcoal prepared from neem leaf powder (AC-NLP) using batch and column studies. Batch adsorption was performed using different variables like adsorbent dose, temperature and contact duration. Thermodynamic analysis of batch treatment concluded that adsorption is thermodynamically feasible and endothermic. This adsorption followed the Pseudo second-order kinetic model derived from correlation coeff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
48
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 120 publications
(52 citation statements)
references
References 36 publications
(34 reference statements)
3
48
0
1
Order By: Relevance
“…Such occurrence is in agreement with the kinetic curves presented in Fig. 2, where it was observed that the adsorption of NM does not occur in an instantaneous way, such behavior in fixed-bed confirms that the adsorption of NM is mainly controlled by chemisorption (Patel 2020). This means that greater bed heights will allow for better performance because the unused fraction of WASC is reduced.…”
supporting
confidence: 90%
“…Such occurrence is in agreement with the kinetic curves presented in Fig. 2, where it was observed that the adsorption of NM does not occur in an instantaneous way, such behavior in fixed-bed confirms that the adsorption of NM is mainly controlled by chemisorption (Patel 2020). This means that greater bed heights will allow for better performance because the unused fraction of WASC is reduced.…”
supporting
confidence: 90%
“…Trong quá trình hấp phụ, chất hấp phụ dạng rắn thường được tách khỏi dung dịch bằng cách lọc qua màng tấm [3], ly tâm [4] hoặc chế tạo vật liệu dạng màng [5]. Hướng nghiên cứu kết hợp các vật liệu hấp phụ với các chất có tính từ tính để dễ dàng tách vật liệu ra khỏi dung dịch bằng nam châm ngoài cũng thu hút sự quan tâm đông đảo của các nhà khoa học trong nước và quốc tế [6][7].…”
Section: Giới Thiệu Chungunclassified
“…Thus, adsorption is a surface phenomenon, requiring more and more active surfaces on the solid phase for efficient adsorption. Various surface-active adsorbents studied for chromium could be classified as lignocellulosic biomass (Çelebi 2020), biochar (Qu et al 2021), zeolites (He et al 2020b), Chitosan (Lei et al 2020), Graphene oxide (Zhang et al 2020), resin (Vilayatkar et al 2020), clay (Ashour and Tony 2020), activated charcoal (Mahmudi et al 2020;Patel 2020) etc. Among lignocellulosic biomass, Picea smithiana cone (Mittal et al 2016), pistachio shell (Banerjee et al 2018) etc.…”
Section: Introductionmentioning
confidence: 99%